Role of immunohistochemistry in cell block sections for categorization of non-small cell carcinoma of lung - Yasmin, Shamoli; Haque, Wasim Selimul; Islam, Sk Md Jaynul; Khondoker, Mostare; Giti, Susane (BIRDEM Medical Journal, 2019)
Background: Computed tomography (CT) guided fine needle aspiration and cytology (FNAC) is a useful modality which aids in early and fairly accurate diagnosis of mass lesions of lungs specially the malignant ones. Previously in patients with primary lung cancer the most important consideration was to discriminate between small cell and non-small cell carcinoma (NSCC) of the lung. With advancement of cancer therapy, sub-typing of NSCC has become very important. The aims of the study were to evaluate the pathological spectrum of the pulmonary diseases in CT guided FNAC of lung mass lesions and utility of limited immunohistochemistry (IHC) in cell block sections to subcategorize NSCC. Methods: The study was carried out at Department of Histopathology in Armed Forces Institute of Pathology from 1st January 2018 to 31st December 2018. It involved total 140 patients who underwent CT guided FNAC in Combined Military Hospital, Dhaka for lung mass lesions. Aspiration was done by pathologist and obtained material was used to make slide smears and cell blocks. Both FNAC smears and cell block sections were examined by histopathologists. The entities diagnosed as NSCC and poorly differentiated carcinomas in FNAC were treated with limited IHC panel in cell block sections. Results: Out of 140 cases 110 were male and 30 were female patients. Age range was from 18 to 85 years, (mean age 60±13.5). Total 83(59%) malignant neoplasms and 57(41%) benign lesions were diagnosed. Among the benign lesions, 28 were diagnosed as granulomatous lesion suggestive of tuberculosis and rests were nonspecific inflammatory lesion. In FNAC smear, small cell carcinoma was diagnosed in 16.9% (14/83) of all malignant lesions, squamous cell carcinoma (SCC) in 26.5% (22/83) patients and adenocarcinoma in 22.9% (19/83) patients. Twenty-five patients were categorized as NSCC as they could not be further subcategorized in FNAC as SCC/adenocarcinoma. Three patients were categorized as poorly differentiated carcinoma as their cytological features could not rule in/out small cell carcinoma. NSCC and poorly differentiated carcinoma diagnosed by FNAC were33.7% (28/83). Cell blocks of all of them were examined, three of NSCC cell blocks were found inadequate for evaluation. All of the rest cases underwent limited IHC panel in cell block sections and were further subcategorized; 13 as SCC and 12 as adenocarcinoma. Total cases of SCC diagnosed in the study after IHC on cell block sections were 35/83(42%) followed by adenocarcinoma 31/83, (33.35%). Conclusion: CT guided FNAC is an effective tool and can be used for fairly accurate and early diagnosis of lung mass lesions. Immunohistochemistry on cell block sections can be used as an effective tool for categorization of NSCC. Birdem Med J 2019; 9(3): 223-228